Again!! No. 4 - Kubo, Mitsurou, 1975- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
"It's day two of the joint practice between the ouendan and the cheerleading club. Having been made ouendan captain for a day, Kinichiro takes the drastic action of ordering Usami to perform the cheerleaders choreography, which supercharges the session, but at the price of Usami's rage"--Back cover.